Uwagi o funkcjonalnych powiązaniach badań pedagogicznych i dydaktycznych z praktyką edukacyjną (na marginesie pewnej dyskusji polonistycznej) = Notes on functional connections between pedagogical and dydactic research and educational practice (a side-note a certain literary discussion) - Pluta, Andrzej (Zielona Góra: Wyższa Szkoła Pedagogiczna)
Functional concept of scientific knowledge is presented in this paper. Its non-epistemological distinctive feature is technological effectiveness. Non-technological, educational and philosophical functional determinante can also be distinguished Considering the first and the second criteria of distinguishing scientific knowledge, the author presents dynamic development of contemporary pedagogical and dydactic thought.
Keywords: badania pedagogiczne; badania dydaktyczne; edukacja